Improving speaking skill through hypno-teaching in Islamic boarding school - Apoko, Tri Wintolo; Yusuf, Maulana (Politeknik Negeri Bali, 2023)
This study investigates the potential of e-portfolios to enhance vocabulary mastery and speaking ability in non-English as Foreign Language (EFL) students. Specifically, it explores the impact of e-portfolios on vocabulary acquisition, speaking fluency, and pronunciation accuracy in a non-EFL setting. The study employs a mixed-methods approach. A quantitative design with pre- and post-intervention tests measures vocabulary knowledge and speaking skills. A qualitative strand uses interviews and document analysis to explore students' perceptions and experiences with e-portfolios. Sixty non-EFL students are randomly assigned to an experimental group using e-portfolios and a control group receiving traditional instruction. Quantitative data is analysed using statistical tests to compare pre- and post-intervention performance between groups. Qualitative data is thematically analysed to identify emergent themes related to students' experiences with e-portfolios. The study expects to demonstrate that e-portfolios can effectively enhance vocabulary mastery and speaking ability in non-EFL students. Findings will contribute to the understanding of e-portfolio implementation in non-EFL contexts and inform pedagogical practices for improving vocabulary speaking skills. This study stands out by investigating the efficacy of e-portfolios in a non-EFL setting, addressing a gap in existing research. Additionally, the mixed-methods approach provides a comprehensive understanding of the impact of e-portfolios on both learning outcomes and learner experiences.